Expression of integrin and CD44 receptors recognising osteopontin in the normal and LPS‐lesioned rat substantia nigra. Issue 3 (22nd May 2013) - Ailane, Sara; Long, Philip; Jenner, Peter; Rose, Sarah
Abstract: The multifunctional protein osteopontin (OPN) is expressed in the substantia nigra (SN) and protects nigral dopaminergic neurones against toxic insult in animal models of Parkinson's disease, although the mechanisms involved are uncertain. In the periphery, OPN regulates inflammatory processes by interacting with integrin and CD44 receptors but the presence and distribution of these sites in SN is unknown. We investigated the expression of integrin receptor subunits and CD44 receptors in the normal SN and after induction of inflammation by lipopolysaccharide (LPS), and their interaction with OPN. In normal rat SN, integrin αv, β3 and β1, and CD44, receptors were expressed on neurones including TH‐positive cells but not on glia. LPS administration induced a loss of TH‐positive neurones in SN and increased expression of glial cells as shown by GFAP, OX‐6 and ED‐1 immunoreactivity. In LPS‐lesioned SN, there was up‐regulation of the expression of integrin β3 and CD44 receptors. Co‐localisation studies showed that this related to their increased expression on OX‐6‐, ED‐1‐ and GFAP‐positive cells. Furthermore, OPN interacted with integrin and CD44 receptors in the normal rat SN as demonstrated by co‐immunoprecipitation and pull‐down techniques. These data show that integrin and CD44 receptors are present on neurones in normal rat SN and that they are up‐regulated on glial cells following LPS‐mediated inflammation in SN, suggesting that they are functionally important in the inflammatory process. The interaction of OPN with these receptors suggests a role in the neuroprotective effect of this protein in the LPS model of Parkinson's disease. Abstract : Integrin and CD44 receptors, that mediate actions of the potential neuroprotective protein OPN in the periphery, are expressed on dopaminergic neurons of the SN and interact with OPN in the brain. Following inflammation, the expression of these receptors is up‐regulated and they are expressed on inflammatory cells implicating a role in regulating the inflammatory process in the SN and thus a potential target for neuroprotection in PD.